BRICK MAKING TRAINING IN PULO VILLAGE, SYAMTALIRA ARUN DISTRICT, ACEH UTARA REGENCY - Rinaldi Mirsa; Eri Saputra (Universitas Muhammadiyah Aceh, 2021)
Brick is an alternative building material made by mixing cement, sand and water which is then molded after a few minutes and then the mold is removed. Then the bricks are aerated during the treatment process before being dried, the bricks must be watered to strengthen, after they are completely dry, the bricks are ready to be used as building materials. The training for making bricks for the community in Pulo Village, Syamtalira Arun District, North Aceh Regency is expected to be an alternative for other livelihoods in the area. The method used is FGD (focus group discussion) followed by training in making bricks and monitoring and evaluation are carried out. Community empowerment activities are to provide information and skills to the Pulo Village community on how to make bricks so that the community can develop their own business for the long term and can be a joint effort to produce bricks. The conclusion of the implementation of community empowerment is to create brick making in accordance with SNI 03-0349-1989 in order to develop home industries, increase knowledge in developing small and medium enterprises.Keywords: Brick, Training, Community, Livelihood